2005
DOI: 10.1038/sj.ejhg.5201353
|View full text |Cite
|
Sign up to set email alerts
|

Patients with familial biparental hydatidiform moles have normal methylation at imprinted genes

Abstract: In molar tissues from patients with recurrent biparental hydatidiform moles, we could previously demonstrate that differentially methylated regions (DMRs) of four imprinted genes are abnormally methylated on the maternal alleles. It remained unclear if this abnormal methylation originated de novo in the molar tissues or if it is even recognizable in the patient somatic tissues. To address this question, we investigated the DNA methylation of four imprinted genes in total blood from the two sister-patients. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…To investigate whether this gain of methylation is the result of an abnormal erasure of the grandparental marks in the primordial germ cells of the patients, we traced the inheritance of the abnormally methylated alleles to the molar tissues and found that the gain of methylation occurred in two cases on unmethylated alleles in the patients. This indicated that the abnormal methylation, at least on these two genes, was acquired de novo either in the maternal germline or post‐zygotically before or after implantation (65). So far, only one study addressed by immunohistochemistry the expression of an imprinted gene, p57 KIP2 , in RHMs caused by defect in 19q13.4 and showed its underexpression (29), which is in agreement with the above‐mentioned methylation data.…”
Section: Epigenetics Of Hmssupporting
confidence: 72%
“…To investigate whether this gain of methylation is the result of an abnormal erasure of the grandparental marks in the primordial germ cells of the patients, we traced the inheritance of the abnormally methylated alleles to the molar tissues and found that the gain of methylation occurred in two cases on unmethylated alleles in the patients. This indicated that the abnormal methylation, at least on these two genes, was acquired de novo either in the maternal germline or post‐zygotically before or after implantation (65). So far, only one study addressed by immunohistochemistry the expression of an imprinted gene, p57 KIP2 , in RHMs caused by defect in 19q13.4 and showed its underexpression (29), which is in agreement with the above‐mentioned methylation data.…”
Section: Epigenetics Of Hmssupporting
confidence: 72%
“…This is also expected, because imprinted expression of this gene depends on the maternal methylation of the KCNQ1OT1 DMR. Finally, the DNA methylation status of investigated DMRs at imprinted genes is normal in the mothers of the affected pregnancies (El-Maarri et al, 2005), further supporting the observation that the imprinting defects arise de novo during female gametogenesis. What might cause the different results at the H19 DMR between these studies?…”
Section: Bihm Have a Global Defect In Reprogramming Or Maintenance Ofsupporting
confidence: 69%
“…A complete mole with p57 positivity was observed in this study ( Table 3 ), suggesting either retention of the maternal chromosome 11 [ 15 ], or a biparental complete mole. Biparental complete moles are generally the result of abnormal methylation of maternal alleles [ 16 ] and usually show complete lack of p57 staining [ 12 ], although maternal homozygous or compound heterozygous mutations in the NLRP7 and C6orf221 (KHDC3L) genes have also been implicated when fetuses are shown to be diploid and biparental in origin [ 17-19 ]. Both the 6q13 C6orf221 (OMIM #614293) and 19q13.42 NLRP7 (OMIM #609661) genes are expressed in oocytes, and are thought to be involved in setting and/or maintaining the maternal imprint [ 19 ], with mutations in the latter thought to be linked to early cleavage errors and subsequent reduced maternal immune response that allows abnormal cells to persist [ 18 ].…”
Section: Discussionmentioning
confidence: 99%